Penapisan dan Identifikasi Bakteri Kitinolitik Penghambat Pertumbuhan Ganoderma boninense in Vitro - Wibowo, Risky Hadi; Mubarik, Nisa Rachmania; Rusmana, Iman; Thenawidjaya, Maggy (Jurnal Fitopatologi Indonesia, 2017)
Chitinolytic bacteria have been reported as biocontrol agents and have the ability to produce chitinase enzymes. The objective of the research was to obtain chitinase producing bacteria that had antagonistic activity to Ganoderma boninense, a causal agent of basal stem rot on oil palm. A total of 63 isolates of chitinase producing bacteria were isolated from soil of Bukit Dua Belas National Park and oil palm plantation in Jambi Province; all was screened for their potency in inhibiting G. boninense in vitro. Three isolates designated TB04-05, SW01-11, and SW02-08 were potentially suppressed and inhibited the mycelium growth of G. boninense in vitro. Based on their specific chitinase activity, these three isolates produced the highest level of chitinase enzyme of 6.3072 U mg-1 protein, 6.0385 U mg-1 protein and 6.1279 U mg-1 protein, respectively after 24 hr incubation. Based on 16S RNA identification, strain TB04-05 had similarity with Bacillus cereus, whereas strains SW01 and SW02-08 had similarity with Bacillus thuringiensis.